Female Wage Inequality in Latin American Labor Markets - Saavedra, Luz A. (World Bank, Washington, DC, 2014)
The author uses quantile regression to document the evolution of the earnings structure of salaried and self-employed female workers in urban areas in three Latin American countries-Argentina, Brazil, and Costa Rica-after structural reforms were introduced. The analysis covers pre- and post-reform years: in Argentina, 1988 and 1997, and in Brazil and Costa Rica, 1989 and 1995. Four primary results emerge from the analysis: 1) After other characteristics are controlled for, wage premiums to human capital, labor experience, and other characteristics vary along the conditional distribution. This indicates that a homoscedastic model is not suitable for analyzing wage differentials among working women in these countries. 2) Wage inequality among women fell in the self-employment sector in all three countries. In the salaried sector results were mixed, with wage inequality declining in Argentina but increasing slightly in Costa Rica. 3) The decline in female wage inequality can be explained in part by changes in the premium to education. Results indicate that the relative premium to education fell in Argentina and Brazil-that is, the adjusted wage differential between more educated and less educated women decreased between the sampled years in these countries. In contrast, wage differentials arising from education increased in Costa Rica. 4) Women earning less than their characteristics would predict seemed to fare well with the economic opening: domestic workers, nonwhite workers, and the least educated in the lower quantiles saw their wage premiums increase relative to those of the control groups. These results are consistent with the predictions of the Heckscher-Ohlin theory of trade liberalization: those with less human capital saw wage gains relative to those with more human capital.